Xanthium strumerium L.: An Ethnomedicinal and Phytochemical Review - Surender Singh Yadav; Showkat Ahmad Ganie; Surender Singh Gulia; Neelam Yadav (International Journal of Phytomedicine, 2014)
Xanthium strumerium L. (Asteraceae), commonly known as “Cocklebur” is an annual herb of wastelands found in North America, Brazil, China, Malaysia and India. It has been traditionally used for its cooling, fattening, anthelmintic, digestive, and antipyretic activities. Different plant parts are predominantly used for curing malarial fever, asthma, rheumatism, leprosy, migraine, small pox and cancer. Leaves of the plant are used for the treatment of eczema, roots against high fever and fruits to treat conjunctivitis. It is also used to cure leucoderma, epilepsy, salivation, congestive heart diseases, nephritis, toxemia of pregnancy, hypertension, premenstrual tension and poisonous bites of insects. Seeds yields edible oil which is used in bladder infection. Based on ethnobotanical information it is found that plants used in folk medicine are rich in bioactive molecules. The review reveals that phytochemical constituents of wide variety have been isolated. Phytoconstituents like anthraquinone, cardenolide, leucoanthocyanin, simple phenolics (catechol) and triterpenoids were reported. Many phytocompounds like caffeic acid, isoxanthanol, xanthanol, xanthiazone, xanthanin, xanthatin etc. were isolated from the plant and proven to be biologically active. The need for review of the plant species was predominantly to answer the gaps between ethnomedicinal uses and phytochemical studies. Hence, the present review article explores the ethnomedicinal uses and phytochemistry of X. strumerium, which upon further research could lead to development of viable drugs for the treatment of variety of ailments. However, there is further need for toxicity and clinical trials on crude extract and isolated phytoconstituents which will help to commercialize.